Decoding Entrepreneurship Education Ecosystems (EEE): A Cross-European Study in Primary, Secondary Schools and Vocational Training - Toutain, Olivier; Mueller, Sabine; Bornard, Fabienne (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This article studies entrepreneurship education as a living ecosystem, on the basis of the ecological metaphor. It contributes to a multidimensional model to analyse Entrepreneurship Education Ecosystems (EEE). This model contains six key dimensions, extracted from the literature review: a/the learning framework; b/networks, connections and relational proximity; c/entrepreneurial culture; d/pedagogical solutions; e/learning spaces and materials; and f/the motivation of its actors. Based on these dimensions, we analyse nine case studies (53 interviews) of best practice programmes across schools in Spain, Germany and Finland to understand how the single actors experience their ecosystem at individual and collective levels.